Travailler langue et culture en jouant avec les lieux, le savoir et la narration - Evain, Christine (Studia Romanica Posnaniensia, 2019)
The storytelling activity coupled with that of playing and sharing a ‘story’ is part of the traditional repertoire of language didactics. In the context of a language project, a group of foreign Master’s students at the Ecole Centrale de Nantes were asked to use two tools: the Baludik (a gamified circuit editor) and eZoomBook (an enriched book editor). Our article reports back on the methodology used to offer students creative activities based on the Baludik and eZoomBook editors, and analyses the students’ results and feedback. Our goal is to suggest possible pedagogical uses of these circuits and book editors, applicable to the learning of different foreign languages.